PENGARUH KEGIATAN EKSTRAKURIKULER, PERCAYA DIRI DAN LITERASI EKONOMI TERHADAP MINAT BERWIRAUSAHA SISWA SMPN DI SURABAYA - Supriyanto, Supriyanto (UNIVERSITAS NEGERI SURABAYA, 2016)
This study aimed to analyze the effect of extracurricular activities , confidence and economic literacy of the students' interest in entrepreneurship junior high schools in Surabaya . This research is quantitative . This study of 233 samples were taken by simple random sampling technique . Analysis of data using multiple linear regression . Partial results of hypothesis testing showed extracurricular activities and economic literacy significant effect on students' interest in entrepreneurship junior high schools in Surabaya while confident no significant effect on students' interest in entrepreneurship junior high schools in Surabaya. Simultaneous hypothesis test results showed extracurricular activities , confidence and economic literacy simultaneously significant effect on students' interest in entrepreneurship junior high schools in Surabaya